‘Nel verso impenetravi la | tua notte’: Appunti per un’eredità pasoliniana nei versi di Amelia Rosselli - Collina, Riccardo (Incontri. Rivista europea di studi italiani, 2024)
“Nel verso impenetravi la | tua notte” Notes for a Pasolinian heritage in Amelia Rosselli’s verses Amelia Rosselli and Pier Paolo Pasolini represent two of the most relevant characters of the second half of the Italian twentieth century. Their diversity and independence, as opposed to other cultural and literary perspectives of that time, are significant and allow for an interesting comparison, particularly with regard to their poetic contexts. Pasolini is always studied as a “complete” intellectual, while Rosselli is recognised as the poet of lapsus and trilingualism. The essay intends to analyse some noteworthy aspects of the relationship between them, starting from Pasolini’s role in introducing Rosselli to the public and proceeding to interpret Pasolini’s presence in several key passages of Amelia Rosselli’s work, from Variazioni belliche to Impromptu. The alleged dependence of Amelia Rosselli regarding the Pasolinian lexicon will be discussed. Pasolini couldn’t help but be astonished by her ability and diversity, even if he himself commits some mistakes of simplification, maybe caused by the excessive rush to be considered as the discoverer of an exceptional poet.